Система дистанційного регулювання опаленням приміщення - Потапов, Г. І. (ХНУРЕ, 2020)
Temperature control is a process in which change of temperature of a space (and objects collectively there within), or of a substance, is measured or otherwise detected, and the passage of heat energy into or out of the space or substance is adjusted to achieve a desired temperature